Development of communication system for IoT based solar irrigation system - Aiman Safwan, Ahmad Suffian (2021)
Agriculture has been the most important practice from the very beginning of the human civilization. This is because agriculture are source of food for human civilization and it is very important to have a good and quality crop. To have the quality crop the farmers have to keep monitor and watering their crop or call as irrigation. In the beginning of agricultural industry, they use the traditional methods for irrigation, such as overhead sprinkler and flood type. This system is not that much efficient. They results in a lot of wastage of water and can also create a disease such as fungus formation due to the over moisture in the soil. Water scarcity is also one of the problems due to the global climatic changes. Water scarcity is mainly man-made due to excess population growth and improper use of water. For the irrigation purposes, farmers will need a lot of water. And for that it is very important and they will need a proper and sustainable way to use water for irrigation without any water loss and wastage. One of the ways to counter this water losses and wastage is by using a proper irrigation system. A sprinkler or drip irrigation system can be implemented to reduce the loss of water. And based on research drip sytem is more efficient than sprinkler. In this modern day, this system can be develop using new technology and can be automated. An automated irrigation system refers to the operation of the system with no or just a minimum of manual intervention beside the surveillance. Almost every system (drip, sprinkler, surface) can be automated with help of timers, sensors or computers or mechanical appliances. By using any microcontroller such as Arduino, Raspbery Pi, NodeMCU it is able to serve numbers of different sensors, at the same time and the markets offer various type and sizes of sensors. The sensor, the timer used was perfect in detecting and sending signal to Arduino, to control the water pump and to open the solenoid valve. It makes the irrigation process more efficient and workers can concentrate on other important farming tasks. On the other hand, such a system can be expensive and very complex in its design and may needs experts to plan and implement it. The aim of this automated irrigation system is to provide a technology that can help ease the operation to the farmer and also in agricultural industry. With this technology, it can be operated anywhere and not worrying about the electricity supply because it is powered by solar. Thus, the main objective of this project is to develop a system that can optimize water, to develop a system that can optimize electricity consumption by using solar, to have fully automated irrigation system and also to have a system that can be monitored by using mobile application.